RIFM fragrance ingredient safety assessment, α-Methylbenzyl acetate, CAS Registry Number 93-92-5. (November 2016) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Abstract: The use of this material under current use conditions is supported by the existing information. This material was evaluated for genotoxicity, repeated dose toxicity, developmental toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity, skin sensitization potential, as well as, environmental safety. Developmental toxicity was determined to have the most conservative systemic exposure derived NO[A]EL of 100 mg/kg/day. A gavage developmental toxicity study conducted in rats on a suitable read across analog resulted in aMOE of 3571 while considering 78.7% absorption from skin contact and 100% from inhalation. A MOE of >100 is deemed acceptable. Highlights: α-Methylbenzyl acetate safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. Developmental toxicity was determined to have the most conservative NO[A]EL. An acceptable MOE was obtained.